Public health and the economy could be served by reallocating medical expenditures to social programs. (December 2017) - Tran, Linda Diem; Zimmerman, Frederick J.; Fielding, Jonathan E.
Abstract: As much as 30% of US health care spending in the United States does not improve individual or population health. To a large extent this excess spending results from prices that are too high and from administrative waste. In the public sector, and particularly at the state level, where budget constraints are severe and reluctance to raise taxes high, this spending crowds out social, educational, and public-health investments. Over time, as spending on medical care increases, spending on improvements to the social determinants of health are starved. In California the fraction of General Fund expenditures spent on public health and social programs fell from 34.8% in fiscal year 1990 to 21.4% in fiscal year 2014, while health care increased from 14.1% to 21.3%. In spending more on healthcare and less on other efforts to improve health and health determinants, the state is missing important opportunities for health-promoting interventions with a strong financial return. Reallocating ineffective medical expenditures to proven and cost-effective public health and social programs would not be easy, but recognizing its potential for improving the public's health while saving taxpayers billions of dollars might provide political cover to those willing to engage in genuine reform. National estimates of the percent of medical spending that does not improve health suggest that approximately $5 billion of California's public budget for medical spending has no positive effect on health. Up to 10, 500 premature deaths could be prevented annually by reallocating this portion of medical spending to public health. Alternatively, the same expenditure could help an additional 418, 000 high school students to graduate. Graphical abstract: Highlights: Medical spending in California rose in 25 years from 14% to 21% of the State budget. In this period spending on public health fell by a similar percentage. California spends $6 billion annually on healthcare that does not improve health. Redirecting this money to tobacco prevention would prevent 12, 300 deaths annually. Redirecting it to education would help an additional 418, 000 students graduate.